Application of Retail Services Quality Scale to Sri Lankan Supermarkets: An Empirical Study - Perera, H.S.C.; Buddhika, S.A.; Rathnayke, C.V. (Indian Journal of Marketing, 2008)
Supermarkets are considered to be the major form of retailing all over the world. Moreover services quality has being long regarded to be a critical element in enhancing the perception of overall merchandise quality in supermarkets. Services quality excellence has been shown to assist in both the retention and expansion of the existing customer base. But only few studies have attempted to identify key dimensions of services quality as well as to investigate the prevailing services quality in the supermarket industry, thus this study attempts to fill this gap by examining the key dimensions of retail service quality across the supermarket industry in Sri Lanka as well as to test the most commonly used scale to measure retail service quality; The Retail Services Quality Scale. Survey method was employed for the study and a structured questionnaire was self-administered among a sample of 300 respondents who were selected from customers who are visiting Cargills Supermarket representing Western&Southern provinces including all six districts, prior to them entering to the supermarket. Cargills supermarket was selected as the research site due to the fact that it is the only supermarket with island wide presence, having 108 supermarkets in Sri Lanka. The questionnaire was based on Retail Service Quality Scale (RSQS) which incorporates five dimensions, namely Physical aspects, Reliability, Personal interaction, Problem-solving&Policy, most commonly used scale in measuring services quality. Thirty questions were developed and used to cover above five areas. Mean comparison and factor analysis techniques were used to analyze data. Study founds out that among all districts higher mean score has being recorded for reliability. When it comes to physical aspects, Southern province records a comparatively higher mean score comparing with western province. Again in Personal interaction and Problem solving Southern province Supermarkets records comparatively high mean score. Policy aspect records comparatively higher mean score among both provinces. Factor analysis identifies six major factors against the five factors identified in the scale.